"Learning by Doing" and "Investment in Training": A Synthesis of Two "Rival" Models of the Life Cycle - Killingsworth, Mark R. (Review of Economic Studies, 1982)
This paper provides a theoretical synthesis of recent discussions of "learning by doing" and "investment in training" as alternative forms of human capital accumulation. These theoretical notions relate to essentially different phenomena; in particular, pace Becker and Mincer, "investment in training" does not completely encompass "learning by doing". The paper then develops a model in which human capital accumulation occurs via both "training" and "learning by doing". The joint training-learning model, since it is more general then "pure" models in which all accumulation occurs via either training or learning, avoids certain restrictive and seemingly implausible implications of either kind of "pure" model. However, the joint model also has implications that, while compatible with stylized facts about the life cycle, are sharper than those of either kind of pure model. (For example, the joint model implies that market time and earnings must rise early in the life cycle, while neither pure model without "corners" does so.) Finally, the notion of learning by doing provides a rationale for an empirical finding that has recently received attention, to the effect that the rate of depreciation of human capital is not constant, but rather depends on the extent to which it is used in market activities.